2021
DOI: 10.1111/joms.12698
|View full text |Cite
|
Sign up to set email alerts
|

You Speak, I Speak: The Social‐Cognitive Mechanisms of Voice Contagion

Abstract: This study examines whether and how constructive voice (i.e., suggestions intended to promote positive changes at work) is contagious. Guided by social cognitive theory, we propose that witnessing a co‐worker’s voice increases an employee’s propensity to engage in voice via two parallel psychological mechanisms: voice self‐efficacy beliefs and voice instrumentality beliefs. Data collected from a vignette experiment (N = 661), an experience‐recall experiment (N = 548), and a field study (N = 549) provide eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 138 publications
(173 reference statements)
0
18
0
1
Order By: Relevance
“…have important positive impacts on the observers themselves, while other studies have suggested that these positive behaviors have negative impacts on the observers. For example, Ng et al 72 argued that witnessing the voice of a coworker may promote observers to engage in this voice. On the contrary, other studies have shown that employees with a high level of creativity may cause the envy of, and ostracism by, their coworkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have important positive impacts on the observers themselves, while other studies have suggested that these positive behaviors have negative impacts on the observers. For example, Ng et al 72 argued that witnessing the voice of a coworker may promote observers to engage in this voice. On the contrary, other studies have shown that employees with a high level of creativity may cause the envy of, and ostracism by, their coworkers.…”
Section: Discussionmentioning
confidence: 99%
“… 71 Similarly, emerging research has shown that when employees witness the voice behavior of their coworkers, their own voice self-efficacy beliefs will be enhanced, which will further trigger their voice behavior. 72 Taken together, it is suggested that serving self-efficacy serves as a conduit that transmits the interaction between the service-oriented OCB of coworkers and the self-serving attribution of observers into their own service-oriented OCB.…”
Section: Theoretical Grounding and Hypothesis Developmentmentioning
confidence: 99%
“…Gist [ 22 ] argued that, since self-efficacy in a special context is more closely related to people’s cognition and behavior, the efficacy of a specific field has a stronger predictive power for corresponding behavior. Previous studies have shown that employees’ voice efficacy can predict their voice behavior [ 55 ]. The strength of confidence in obtaining the desired effect of voice directly affects employees’ voice intentions.…”
Section: The Literature Review and Research Hypothesismentioning
confidence: 99%
“…The results obtained that social cognitive theory which consists of behavior, cognitive and situational factors described through social, cognitive and teacher presence, as a case study framework on online and distance learning, provides an alternative how to condition learning that can be built in situations online during the covid-19 pandemic. Meanwhile, other applications are found in the business sector [38]- [41], in the criminal sector [42], and in the information and management sector [43], [44]. Based on the search results, the researchers concluded that social cognitive learning is still not widely applied in the field of mathematics education.…”
Section: Introductionmentioning
confidence: 99%